Implementasi Model Pembelajaran Multiliterasi dalam Mengembangkan Keterampilan HOTS Siswa pada Pembelajaran Bahasa Indonesia di MTs Darut Tauhid Tanjung Sari - Hemas Haryas Harja Susetya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Indonesian language learning in madrasahs is still dominated by conventional teacher-centered approaches that fail to foster students’ higher order thinking skills (HOTS). This condition calls for innovative learning models that encourage students to think critically, creatively, and reflectively. This study aims to describe the implementation of a multiliteracy learning model in developing students’ HOTS in Indonesian language learning at MTs Darut Tauhid Tanjung Sari. The research employed a descriptive qualitative approach involving one Indonesian language teacher and 17 eighth-grade students as participants. Students demonstrated improvement in three key HOTS aspects: analyzing (88%), evaluating (76%), and creating (82%). The learning process became more interactive and student-centered, with active participation in reading, writing, and discussion activities using diverse textual and visual media. The teacher acted as a facilitator who guided students’ critical and reflective thinking processes through open-ended questioning and collaborative learning. The study concludes that the multiliteracy model is effective in developing students’ HOTS while simultaneously fostering creativity, self-confidence, and critical awareness.